1995
DOI: 10.1128/jb.177.11.2998-3003.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptomyces albus 18-kilodalton heat shock-responsive protein

Abstract: In Streptomyces albus during the heat shock response, a small heat shock protein of 18 kDa is dramatically induced. This protein was purified, and internal sequences revealed that S. albus HSP18 showed a marked homology with proteins belonging to the family of small heat shock proteins. The corresponding gene was isolated and sequenced. DNA sequence analysis confirmed that the hsp18 gene product is an analog of the 18-kDa antigen of Mycobacterium leprae. No hsp18 mRNA could be detected at 30؇C, but transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 30 publications
0
46
1
Order By: Relevance
“…In contrast to E. coli, the deletion of hsp16.6 in Synechocystis sp. strain PCC 6803 resulted in a clear growth defect after heat shock treatment (177,178) and disruption of hsp18 in Streptomyces albus showed that the gene is required for thermotolerance at extreme temperatures (275). Thus, there is cumulative in vivo evidence that ␣-Hsps do play a physiological role in the protection against adverse conditions.…”
Section: Position Of ␣-Heat Shock Proteins In a Multichaperone Networkmentioning
confidence: 99%
“…In contrast to E. coli, the deletion of hsp16.6 in Synechocystis sp. strain PCC 6803 resulted in a clear growth defect after heat shock treatment (177,178) and disruption of hsp18 in Streptomyces albus showed that the gene is required for thermotolerance at extreme temperatures (275). Thus, there is cumulative in vivo evidence that ␣-Hsps do play a physiological role in the protection against adverse conditions.…”
Section: Position Of ␣-Heat Shock Proteins In a Multichaperone Networkmentioning
confidence: 99%
“…A considerable amount of data support a role for sHsps in the acquisition of thermotolerance to high temperature (Vierling, 1991(Vierling, , 1997Arrigo and Landry, 1994), although in some organisms or under some environmental conditions their function may be redundant with other cellular components (Petko and Lindquist, 1985;Servant and Mazodier, 1995;Wotton et al, 1996). Gain-of-function experiments in mammalian and Drosophila cells have shown that constitutive expression of sHsps confers some thermotolerance (Arrigo and Landry, 1994), and expression of plant sHsps in E. coli has also been reported to enhance hightemperature tolerance (Yeh et al, 1997;Soto et al, 1999).…”
Section: Protein Refolding Facilitated By a Small Heat Shock Proteinmentioning
confidence: 99%
“…Transcription of hsp18, encoding a small HSP (smHSP) highly expressed in S. albus, was also analysed (Servant and Mazodier, 1995). Its regulation is likely to be different from that of the groEL genes, as no CIRCE motif is present in the hsp18 promoter region.…”
Section: Disruption Of S Albus Hsprmentioning
confidence: 99%
“…albus RNA was extracted and Northern blotting was performed as previously described (Servant and Mazodier, 1995;Servant et al, 1994). Hybridization was carried out under highly stringent conditions and blots were washed with 0.5× SSC-0.1% SDS at 65ЊC.…”
Section: Rna Analysismentioning
confidence: 99%
See 1 more Smart Citation